PENGARUH LITERASI KEUANGAN, KUALITAS PELAYANAN DAN PROSEDUR KREDIT TERHADAP KEPUTUSAN KREDIT NASABAH BPR KOTA BATAM - Sartika, Dewi; L. Tobing, Vargo Christian (LPPM Universitas Putera Batam, 2024)
variables Along with the development of capital needs at the present time has brought bankers into anera of very strict competition to challenge capital seekers as customers. The aim of this study is to lookat the influence of financial literacy variables (X1), quality of service (X2) and credit procedures (X3)on credit decisions. (Y). This research uses a quantitative approach, using a survey method, where thedata collection method is carried out directly from the source. The population used in this study is BPRCustomer Barelang Independent and BPR Fund Makmur registered with the Financial ServicesAuthority (OJK) of Batam City during the year 2023 with a sample number of 184 people. The resultsof the research were demonstrated through the T-Test, the financial literacy variable recorded in partdid not significantly affect the credit decision of the customer of BPR Kota Batam. The service qualityvariable and the credit procedure have a partial influence on the customer's credit decision. TheAdjusted R Square determination coefficient is 0.295 or 29.5%, which means that financial literacy,quality of service and credit procedures are at 29.5% presentation, while the remaining 70.5% areinfluenced by other